Moderation, negative nationalism and extremism from the viewpoint of the Risale-I Nur - Akhmetova, Elmira; Abdul Rahim, Adibah (International Scientific Researches Association(ISCIRA), 2019)
This paper analyses the ideas of Said Nursi (1876-1960) on the importance of moderation (wasatiyyah) in the way of combatting extremism, racism and radicalism, which are sharply escalating in our days both in the East and the West. The first part of the paper finds that, according to Nursi, moderation was the main principle of the Islamic way of life, capable to provide well-being and happiness for humanity. The next part of the paper highlights the positive role of moderation in creating unity and solidarity as a solution, which is capable to provide happiness and security for all humans regardless of their religious, ethnic or social backgrounds. It, also, suggests that Nursi identified nationalistic and patriotic sentiments as radical and extremist, which were artificially evoked among the Muslim nations and are alien to the Islamic approach of moderation. After studying the Risale-i Nur approach towards the followers of other mazhabs and non-Muslims, the paper concludes that Nursi condemned all types of extremist ideas and actions as they were harmful for healthy progress and wellbeing of humanity.